IMPROVING THE SPEAKING SKILLS OF VIII GRADERS AT SMPN 10 PONTIANAK THROUGH STORY TELLING - Fuji Andayani (STBA Pontianak, 2018)
This study aimed at improving the English speaking skills of the students of grade VIII at SMPN 10 Pontianak through story telling. This was classroom action research using Kemmis dan McTaggart model: planning, action, observation and reflection. The result showed, in storytelling, all students reached the minimum standard score of 7, even more students scored above 7. In the interactions, the result of the students’ improvement was described from the frequency of their producing English based on the categories. In the 1st cycle, 17 out of 28 students were categorized as good category. There were 6 students who are categorized as average and 5 students who were classified into very good category. There was no student categorized as excellent category. In the 2nd, 19 students out of 28 students were categorized as very good category and 9 students who were classified into good category. There was no more student who categorized as average. There was no student categorized as excellent category.This means that the students’ speaking skill has improved through story telling. It is found that story telling is one of the techniques which is useful to improve the students’ speaking skills.